Polydopamine coated TiO2 nanofiber fillers for polyethylene oxide hybrid electrolytes for efficient and durable all solid state lithium ion batteries. Issue 3 (5th January 2022) - Zhao, Erqing; Guo, Yudi; Zhang, Awei; Wang, Hongliang; Xu, Guangri
Abstract : Polydopamine coated TiO2 nanofiber fillers have been synthesized by the hydrothermal method combined with PDA coating, and can significantly enhance the electrochemical properties and interfacial stability of the PEO polymer electrolyte. Abstract : The polyethylene oxide (PEO) solid electrolyte is a promising candidate for all solid state lithium-ion batteries (ASSLIBs), but its low ionic conductivity and poor interfacial compatibility against lithium limit the rate and cycling performance of the cell. Herein, the novel and efficient TiO2 @polydopamine (PDA) fillers have been synthesized by coating PDA onto the surface of the TiO2 nanofibers, which are then incorporated into PEO matrices to form the composite electrolyte. The composite electrolyte displays a higher ionic conductivity of 4.36 × 10 −4 S cm −1, a wider electrochemical window up to about 5 V and a higher t Li + of 0.190 at 55 °C compared to the PEO electrolyte. Additionally, the Li/composite electrolyte/Li batteries show a stable Li plating/stripping cycle performance, indicating good interfacial compatibility between the composite electrolyte and lithium. Thus, the LiFePO4 /Li ASSLIBs display a fantastic rate performance and cycling stability, and deliver superior discharge specific capacities of 153.83 and 136.45 mA h g −1 at current densities of 0.5C and 2C, achieving good capacity retentions of 93.27% and 91.23% at 0.5C and 1C after 150 cycles, respectively. Therefore, the PEO–TiO2 @PDA composite electrolyte is a potential solid electrolyte for ASSLIBs.